Відомо, що a/b = c/d. Доведи, що: 1) (a-b)/b = (c-d)/d; 2) (a+b)/b = (c+d)/d.

влад2262 влад2262    3   17.04.2019 01:20    4

Ответы
nikitos15012 nikitos15012  17.04.2019 01:20
Відповідь:

1) a/b = c/d. Віднімемо одиницю від обох частин рівності:
a-b - 1 = c/d - 1; a/b - b/d = c/d - d/d; (a-b)/b = (c-d)/d.
Рівність доведено.
2) a/b = c/d. Додамо одиницю до обох частин рівності:
a/b + 1 = c/d + 1; a/b + b/b = c/d + d/d; (a+b)/b = (c+d)/d.
Рівність доведено.
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Другие предметы